2017
DOI: 10.3389/fpls.2017.01366
|View full text |Cite|
|
Sign up to set email alerts
|

Phytohormone and Putative Defense Gene Expression Differentiates the Response of ‘Hayward’ Kiwifruit to Psa and Pfm Infections

Abstract: Pseudomonas syringae pv. actinidiae (Psa) and Pseudomonas syringae pv. actinidifoliorum (Pfm) are closely related pathovars infecting kiwifruit, but Psa is considered one of the most important global pathogens, whereas Pfm is not. In this study of Actinidia deliciosa ‘Hayward’ responses to the two pathovars, the objective was to test whether differences in plant defense responses mounted against the two pathovars correlated with the contrasting severity of the symptoms caused by them. Results showed that Psa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 80 publications
(120 reference statements)
3
29
0
Order By: Relevance
“…Limited bacterial progression within plant tissues is regarded as a tolerance trait. However, until now very few long-term disease assessments under the same controlled environmental conditions have been performed to compare Psa-and Pfm-inoculated A. chinensis and A. arguta plants, hindering the full comprehension of bacterial infection and plant tolerance mechanisms (Wurms et al, 2017a). Datson et al (2015) reported that in A. arguta plants stab-inoculated with a Psa strain, the endophytic bacterial population was lower and more restricted to the site near the inoculation zone when compared with A. chinensis, even four weeks after inoculation.…”
Section: Bacterial Progression Is More Restricted In a Argutamentioning
confidence: 99%
See 3 more Smart Citations
“…Limited bacterial progression within plant tissues is regarded as a tolerance trait. However, until now very few long-term disease assessments under the same controlled environmental conditions have been performed to compare Psa-and Pfm-inoculated A. chinensis and A. arguta plants, hindering the full comprehension of bacterial infection and plant tolerance mechanisms (Wurms et al, 2017a). Datson et al (2015) reported that in A. arguta plants stab-inoculated with a Psa strain, the endophytic bacterial population was lower and more restricted to the site near the inoculation zone when compared with A. chinensis, even four weeks after inoculation.…”
Section: Bacterial Progression Is More Restricted In a Argutamentioning
confidence: 99%
“…Although SAM is the precursor of not only ET but also of polyamines, due to its key regulatory role during the first step of ET biosynthesis it is frequently used as reporter for ET metabolism (Zhao et al, 2017). Genes involved in ET biosynthesis, such as AP2/ERF, EIN2 and SAM, were found to be upregulated just 2 dpi in A. chinensis plants inoculated with Psa (Wurms et al, 2017a;Wurms et al, 2017b, Nunes da Silva et al, 2019. LOX1 increased activity was also previously reported in A. chinensis and A. arguta Psa-and Pfm-inoculated plants, and is regarded as a strategy used by the pathogen to antagonize plant defense mechanisms (Cellini et al, 2014;Nunes da Silva et al, 2019).…”
Section: Primary and Secondary Metabolism Ismentioning
confidence: 99%
See 2 more Smart Citations
“…The AP2 transcription factors and ERF transcription factors belong to the AP2/ERF superfamily, which has been proven to participate in various resistance responses [ 44 , 45 ].In the study of P. syringae, which causes various diseases in crops including kiwifruit, the expression of specific AP2/ERF transcription factors enhanced disease resistance in tobacco and Arabidopsis, respectively [ 46 , 47 , 48 ]. Wurms et al found that Psa infection caused an upregulation of AP2/ERF2 transcription factor in kiwifruit [ 49 ].…”
Section: Discussionmentioning
confidence: 99%